ANALYSIS OF DIFFICULTY IN DESIGNING LEARNING SCIENCE IN ELEMENTARY SCHOOL - Ramdhan Witarsa; Asep Solihat; Dini Nurhasanah; Nia Karlina (PrimaryEdu : Journal of Primary Education, 2018)
Learning science is a learning done in Elementary School (ES). During this time, science learning is still felt difficult by most teachers and prospective ES teachers. These difficulties include difficulty in designing learning. These difficulties affect the readiness and ability of teachers in implementing learning in the classroom. The purpose of this study is to analyze the difficulties experienced by the PGSD study program in terms of planning science learning in ES. The research method used is descriptive quantitative research method. The population of this research is the students of PGSD IKIP Siliwangi who take the course of Learning Planning in ES as many as 50 students. The sampling method used purposive sampling technique, which is apprentice applicant 1 who get the learning planning in ES as much as 25 students. The data collected were questionnaire and data analysis using mode. The results showed that the sequence of the most difficult steps to the easiest in planning science teacher candidate elementary as follows: 1). Mapping SK / KD and indicators; 2). Determining indicators; 3). Determining effective weeks; 4). Arrange syllabus; 5). Establish an assessment; 6). Preparing RPP; 7). Prepare teaching materials.